Prognostic Value of Preoperative Serum Calcitonin Levels for Predicting the Recurrence of Medullary Thyroid Carcinoma - Park, Hyunju; Park, So Young; Park, Jun; Choe, Jun Ho; Chung, Man Ki; Woo, Sook-Young; Choi, Joon Young; Kim, Sun Wook; Chung, Jae Hoon; Kim, Tae Hyuk (Frontiers in Endocrinology, 2021)
Background: Serum calcitonin level is a useful biomarker for predicting primary tumor size, the extent of lymph node, and distant metastasis in patients with medullary thyroid carcinoma (MTC). However, the association between preoperative serum calcitonin levels and long-term oncologic outcomes has not yet been established. The aims of this study were to determine the preoperative serum calcitonin cut-off value for predicting disease recurrence and to evaluate its prognostic value. Methods: Patients with MTC (n = 169) who were treated at a tertiary referral hospital in Korea between 1995 and 2019 were enrolled. To determine the preoperative serum calcitonin cut-off value for predicting structural recurrence, the maximum of the standardized log-rank statistics of all possible cut-off values was used. Multivariable Cox regression analysis was used to determine prognostic factors for disease-free survival. Results: The overall disease-free survival rate was 75.7%. The preoperative serum calcitonin cut-off value that predicted structural recurrence was 309 pg/mL. Preoperative serum calcitonin levels of > 309 pg/mL were the strongest independent predictor of disease recurrence (hazard ratio (HR) 5.33, 95% confidence interval (85% CI) 1.67–16.96; P = 0.005). Lateral lymph node metastasis (HR 3.70, 95% CI 1.61–8.51; P = 0.002) and positive resection margins (HR 3.57, 95% CI 1.44–8.88; P = 0.006) were also significant predictors of disease recurrence. Conclusions: The preoperative serum calcitonin cut-off value is useful in clinical practice. It is also the best predictive factor for disease-free survival. Preoperative serum calcitonin levels may help determine the optimal postoperative follow-up strategy for patients with MTC.